2018
DOI: 10.2147/opth.s164641
|View full text |Cite
|
Sign up to set email alerts
|

Myopia prevalence and risk factors in children

Abstract: PurposeTo evaluate the prevalence and risk factors for pediatric myopia in a contemporary American cohort.MethodsA cross-sectional study of pediatric patients enrolled in the Kaiser Permanente Southern California health plan was done. Eligible patients were 5- to 19-years old between January 1, 2008, through December 31, 2013, and received an ophthalmologic or optometric refraction. Electronic medical records were reviewed for demographic data, refraction results, and exercise data. Prevalence and relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 37 publications
11
70
1
1
Order By: Relevance
“…We also found that the prevalence of myopia in girls was higher than that in boys, which was consistent with the findings in other Chinese locations, such as Guangzhou [15] and Xichang [24]. Previous studies indicated that older children had a higher risk of myopia [2,15,25], which was further confirmed by our study.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the prevalence of myopia in girls was higher than that in boys, which was consistent with the findings in other Chinese locations, such as Guangzhou [15] and Xichang [24]. Previous studies indicated that older children had a higher risk of myopia [2,15,25], which was further confirmed by our study.…”
Section: Discussionsupporting
confidence: 92%
“…18 When only rural areas are considered; however, prevalence of myopia in that study (16.3%) was slightly higher than that of our study. 18 Previous studies conducted in China, [23][24][25][26][27][28][29] South Korea, 30 Australia, 32 France, 33 and the USA 34 reported higher prevalence of myopia, while studies conducted in India, 35 Saudi Arabia, [36][37][38] Brazil, 39 and Paraguay 40 reported lower prevalence than that reported presently. These differences may occur due to differences in subject ages, cut-off thresholds for myopia diagnosis, or methods of measurement (cycloplegia or noncycloplegia).…”
Section: Discussionmentioning
confidence: 89%
“…Myopia was also common in a diverse Southern Californian pediatric cohort and children of Asian ancestry had the highest prevalence. Particular lifestyle habits in different populations may partially explain dissimilarities in myopia prevalence [62]. It has been suggested that a probable causative role in the development of myopia is the competitive and stressful education systems in some East Asian countries [83].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of myopia at the final time-point was 17.9% and was not associated with physical activity. In an American cohort, exercise was associated with a lower rate of myopia [62]. Tideman et al found that myopic children (n = 5711, six-year-old children) in Europe spent less time outdoors, have lower vitamin D3 and higher body mass index than non-myopic children [23].…”
Section: Risk Factormentioning
confidence: 99%